Neuroinflammatory paradigms in lysosomal storage diseases - Bosch, Megan E.; Kielian, Tammy (Frontiers in Neuroscience, 2015)
Lysosomal storage diseases (LSDs) include approximately 70 distinct disorders that collectively account for 14% of all inherited metabolic diseases. LSDs are caused by mutations in various enzymes/proteins that disrupt lysosomal function, which impairs macromolecule degradation following endosome-lysosome and phagosome-lysosome fusion and autophagy, ultimately disrupting cellular homeostasis. LSDs are pathologically typified by lysosomal inclusions composed of a heterogeneous mixture of various proteins and lipids that can be found throughout the body. However, in many cases the CNS is dramatically affected, which may result from heightened neuronal vulnerability based on their post-mitotic state. Besides intrinsic neuronal defects, another emerging factor common to many LSDs is neuroinflammation, which may negatively impact neuronal survival and contribute to neurodegeneration. Microglial and astrocyte activation is a hallmark of many LSDs that affect the CNS, which often precedes and predicts regions where eventual neuron loss will occur. However, the timing, intensity, and duration of neuroinflammation may ultimately dictate the impact on CNS homeostasis. For example, a transient inflammatory response following CNS insult/injury can be neuroprotective, as glial cells attempt to remove the insult and provide trophic support to neurons. However, chronic inflammation, as seen in several LSDs, can promote neurodegeneration by creating a neurotoxic environment due to elevated levels of cytokines, chemokines, and pro-apoptotic molecules. Although neuroinflammation has been reported in several LSDs, the cellular basis and mechanisms responsible for eliciting neuroinflammatory pathways are just beginning to be defined. This review highlights the role of neuroinflammation in select LSDs and its potential contribution to neuron loss.